PENGARUH EDIBLE COATING BERBAHAN DASAR PATI SAGU TUNI (Metroxylon rumphii) TERHADAP MUTU BUAH TOMAT SELAMA PENYIMPANAN - Rachel Breemer; Priscillia Picauly; Nurhayati Hasan (Universitas Pattimura, 2017)
This research was aimed to determine the exact glycerol concentration in the making of edible coating to coat the tomatoes so that the shelf life is extended and the quality is maintained. A Completely Randomized Design with one factor (RAL): glycerol concentration (without coating, 10%, 30%, 50%) was applied. The observed variables were weight shrinkage, color, hardness, total acid and vitamin C. Results showed that for 10 days storage period, the best response of the variables observed was obtained by tomatoes treated with edible coating 10% glycerol concentration that can maintain the quality of tomato and economically feasible than glycerol concentration of 30% and 50%.